Interview The Method of Collecting Research Information - Zueva K. V. (Zien Journals, 2023)
The article analyzes the concept of the interview genre, the level of training of interviewers, reveals possible errors during this procedure, specifies some informal interview rules. The complexity of selecting qualified residents to obtain information about a socially significant person or event is considered
Keywords: interview; interview genre; interviewer; respondent